Flipping the paradigm: a qualitative exploration of research translation centres in the United Kingdom and Australia - Tracy Robinson; Helen Skouteris; Prue Burns; Angela Melder; Cate Bailey; Charlotte Croft; Dmitrios Spyridonidis; Helena Teede (BMC, 2020)
Abstract Background Over the past decade, Research Translation Centres (RTCs) have been established in many countries. These centres (sometimes referred to as Academic Health Science Centres) are designed to bring universities and healthcare providers together in order to accelerate the generation and translation of new evidence that is responsive to health service and community priorities. This has the potential to effectively 'flip' the traditional research and education paradigms because it requires active participation and continuous engagement with stakeholders (especially service users, the community and frontline clinicians). Although investment and expectations of RTCs are high, the literature confirms a need to better understand the processes that RTCs use to mobilise knowledge, build workforce capacity, and co-produce research with patients and the public to ensure population impact and drive healthcare improvement. Methods Semi-structured interviews were conducted with selected leaders and members from select RTCs in England and Australia. Convenience sampling was utilised to identify RTCs, based on their geography, accessibility and availability. Purposive sampling and a snowballing approach were employed to recruit individual participants for interviews, which were conducted face to face or via videoconferencing. Interviews were recorded, transcribed verbatim and analysed using a reflexive and inductive approach. This involved two researchers comparing codes and interrogating themes that were analysed inductively against the study aims and through meetings with the research team. Results A total of 41 participants, 22 from England and 19 from Australia were interviewed. Five major themes emerged, including (1) dissonant metrics, (2) different models of leadership, (3) public and patient involvement and research co-production, (4) workforce development and (5) barriers to collaboration. Conclusions Participants identified the need for performance measures that capture community impact. Better aligned success metrics, enhanced leadership, strategies to partner with patients and the public, enhanced workforce development and strategies to enhance collaboration were all identified as crucial for RTCs to succeed.